Factorization of European and American option prices under complete and incomplete markets - Ibáñez, Alfredo (Journal of Banking & Finance, 2008)
In a standard option-pricing model, with continuous-trading and diffusion processes, this paper shows that the price of one European-style option can be factorized into two intuitive components: One robust, X0, which is priced by arbitrage, and a second, Π0, which depends on a risk orthogonal to the traded securities. This result implies the following: (1) In an incomplete market, these parts represent the price of a hedging portfolio, which is unique, and a premium, which depends only on the risk premiums associated with the residual risk, respectively. (2) In a complete market, it allows factoring the contribution of the different sources of risk to the final option price. For example, in a stochastic volatility model, we can quantify the impact on the option price of volatility risk relative to market risk, Π0 and X0, respectively. Hence, certain misspricings in option markets can be directly related to the premium, Π0. (3) Moreover, these results extend to American securities, which have a third component – an additional early-exercise premium.